Local variations in integration policies: experiences from the perspectives of immigrants in Sweden. (27th April 2023) - Lidén, Gustav; Nyhlén, Jon
This study examines variations in the perception of local integration policy among Swedish immigrants by focusing on community size as an influential determinant for how such policies are experienced. The experiences concern immigrants' relations to two core actors of Swedish integration policy: the public employment service (PES) and the municipalities. The empirical material consists of 28 narrative interviews, and a comparative strategy is applied to categorise participants based on whether they reside in a large or small municipality. While immigrants residing in small municipalities have more of a positive experience of the municipality and a negative view of the PES, interviewed immigrants residing in large municipalities have positive views of the PES and more ambiguous experiences with the municipality.